Recurrent intestinal metaplasia at the gastroesophageal junction following endoscopic eradication of dysplastic Barrett’s esophagus may not be benign - Cameron, Georgina R.; Desmond, Paul V.; Jayasekera, Chatura S.; Amico, Francesco; Williams, Richard; Macrae, Finlay A.; Taylor, Andrew C. F. (Endoscopy International Open, 2016)
Background and study aims: Radiofrequency ablation (RFA) combined with endoscopic mucosal resection (EMR) is effective for eradicating dysplastic Barrett’s esophagus. The durability of response is reported to be variable. We aimed to determine the effectiveness and durability of RFA with or without EMR for patients with dysplastic Barrett’s esophagus.Patients and methods: Patients with dysplastic Barrett’s esophagus referred to two academic hospitals were assessed with high definition white-light endoscopy, narrow-band imaging, and Seattle protocol biopsies. EMR was performed in visible lesions. RFA was performed at 3-month intervals until complete remission of dysplasia (CR-D) and intestinal metaplasia (CR-IM) was achieved.Results: In total, 137 patients received RFA (78 with EMR); 75 with over 12 months follow-up since commencing RFA. Pretreatment histology was intramucosal cancer (IMC) 21 %, high grade dysplasia (HGD) 54 %, low grade dysplasia (LGD) 25 %. CR-D rates were 88 %, 92 %, and 100 % at 1, 2, and 3 years; CR-IM rates were 69 %, 74 %, and 81 %. Kaplan–Meier analysis showed increasing probability of achieving CR-D/CR-IM over time. Of 26 patients maintaining CR-IM for > 12 months, five relapsed with intestinal metaplasia (19 %), and three with dysplasia (12 %). Recurrences occurred in patients with prior HGD/IMC, predominantly at the gastroesophageal junction (GEJ). None relapsed with cancer. Adverse events occurred in 4 % of RFA and 6.5 % of EMR procedures.Conclusions: RFA combined with EMR is effective in achieving CR-D/CR-IM in the majority of patients with dysplastic Barrett’s esophagus, with an incremental response over time. While durable in the majority, recurrent intestinal metaplasia and dysplasia, frequently occurring at the GEJ, suggest long-term surveillance is warranted in high risk groups.